Peningkatan Proses dan Hasil Belajar IPAS Menggunakan Metode Outdoor Learning di Kelas V SDN 178/II Purwasari - Tri Eka Suroja; Megawati; Reni Guswita (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research is based on initial observations that show the low process and results of students' learning science, seen from the UTS IPAS score only reaching 56.6%. The purpose of the study was to determine the Outdoor learning method in improving the process and results of learning science. The research method used is Classroom Action Research. The research was carried out in two cycles, consisting of planning, implementation, action, observation, reflection. The research was conducted on 23 students of class V SDN 178/II Purwasari. The data collection instruments used were observation sheets and learning test questions, data analysis techniques using qualitative and quantitative approaches. The results obtained from this study were: the student learning process in cycle I meeting I 56.5%, meeting II 73.8%, cycle II meeting I 82.6%, meeting II 86.9%. teacher performance cycle I meeting I 86.9%, meeting II 95.6%, Cycle II meeting I 99.9%, meeting II 99.9%, Student learning outcomes in cycle I were 65.2% and in cycle II were 82.6%. From the results of the study it can be concluded that the application of the Outdoor learning method can improve the Process and Results of students' IPS learning.